Cultivating Green Excellence : How Sustainable Talent Management Transforms HR Performance in Eco-Friendly Hotels of Central Java - Ray Octafian; Dyah Palupiningtyas; Nina Mistriani; Krisnawati Setyaningrum Nugraheni (International Forum of Researchers and Lecturers, 2024)
This study examines the impact of green talent management practices on HR performance quality in eco-friendly hotels in Central Java, Indonesia, using a phenomenological approach. Through in-depth interviews with 24 participants across six star-rated hotels, direct observation, document analysis, and focus group discussions, the research explores how green HRM practices influence employee performance and career development opportunities for young talent. The findings reveal that eco-friendly hotels have implemented various green talent management practices including environmentally-conscious recruitment, sustainability training, green performance management, and employee involvement in environmental initiatives. These practices positively impact multiple dimensions of employee performance: task performance through improved resource efficiency; contextual performance through enhanced teamwork; adaptive performance through increased innovation capability; and environmental performance through strengthened pro-environmental behaviors. The effectiveness of these practices is influenced by top management commitment, integration with business strategy, training quality, organizational culture, and resource availability. Young employees perceive involvement in green initiatives as valuable for developing leadership skills, expanding professional networks, and enhancing market competitiveness, although they identify the need for clearer sustainability-focused career paths. The study contributes to GHRM and talent management literature by explicating the mechanisms linking green talent management with performance outcomes in the hospitality industry context, while providing practical implications for hotel managers seeking to enhance both environmental sustainability and human resource performance. The research underscores the importance of a holistic approach to green talent management that aligns environmental priorities with employee development and organizational strategy.